Investments : principles of portfolio and equity analysis - McMillan, Michael G. (CFA Institute investment series., 2011)
A comprehensive guide to investment analysis and portfolio management by an expert team from the CFA Institute In a world of specialization, no other profession likely requires such broad, yet in-depth knowledge than that of financial analyst. Financial analysts must not only possess a broad understanding of the financial markets-including structure, organization, efficiency, portfolio management, risk and return, and planning and construction-but they must also have a strong sense of how to evaluate industries and companies prior to engaging in an analysis of a specific stock. Investments: Pr.